Prevalence of self-reported systemic arterial hypertension in urban and rural environments in Brazil: a population-based study Prevalencia de hipertensión arterial sistémica autorreferida en los ambientes urbano y rural de Brasil: un estudio de base poblacional Prevalência de hipertensão arterial sistêmica autorreferida nos ambientes urbano e rural do Brasil: um estudo de base populacional - Jessica Pronestino de Lima Moreira; José Rodrigo de Moraes; Ronir Raggio Luiz (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The aims of this paper were to estimate the prevalence rates of self-reported high blood pressure among adults in urban and rural environments in Brazil and identify possible associations stratified according to household location. Data from the Brazilian National Household Sample Survey (PNAD) was used, incorporating information from the sampling plan. Logistic regression was used to obtain the odds ratio (OR) as a measure of association between variables and the outcome. The prevalence of self-reported high blood pressure in Brazil was 20.9%: 21% in urban areas and 20.1% in rural areas (OR = 1.06). In both areas, the likelihood of reporting high blood pressure increased with age and women, former smokers, migrants and individuals with morbidities, non-white individuals and individuals with health insurance were more likely to report this disease. Also, in both rural and urban areas, prevalence of high blood pressure was lower among workers and decreased with increasing levels of schooling. All variables showed an association with self-reported high blood pressure in both rural and urban areas, but differences in magnitude were observed in relation to sex and age group. These differences could help justify the promotion of better access and intervention methods at prevention clinics for different population groups. Este artículo tiene por objetivo estimar las prevalencias de la hipertensión arterial sistémica autorreferida de adultos, en los ambientes urbano y rural de Brasil, e identificar posibles asociaciones, estratificadas por situación del domicilio. Se utilizó el Estudio Nacional por Muestra de Domicilios (PNAD), incorporando la información del mismo. Se utilizaron regresiones logísticas para obtener las medidas de asociación odds ratio (OR). La prevalencia de hipertensión arterial sistémica autorreferida en Brasil fue de un 20,9%, siendo un 21% (urbana) y un 20,1% (rural) (OR = 1,06). En ambas áreas, la oportunidad de informar sobre hipertensión arterial sistémica aumentó con la edad, fue mayor entre las mujeres, ex-fumadores, emigrantes, portadores de enfermedades, los de color/raza no blanca e individuos con plan de salud. También en las dos áreas, la hipertensión arterial sistémica fue menor entre los trabajadores y disminuyó con el aumento del número de años de estudio. Todas las variables se mostraron asociadas con la hipertensión arterial sistémica autorreferida, en ambas áreas, no obstante, pudieron ser observadas diferencias en las magnitudes en sexo y franja de edad. Estas diferencias pueden ayudar a encontrar la mejor forma de intervenir en los servicios de prevención y acceso de cada población. Este artigo objetiva estimar as prevalências da hipertensão arterial sistêmica autorreferida de adultos nos ambientes urbano e rural do Brasil e identificar possíveis associações, estratificadas por situação do domicílio. Utilizou-se a Pesquisa Nacional por Amostra de Domicílios (PNAD), incorporando as informações do plano amostral. Regressões logísticas foram utilizadas para obter as medidas de associação odds ratio (OR). A prevalência da hipertensão arterial sistêmica autorreferida no Brasil foi 20,9%, sendo 21% (urbana) e 20,1% (rural) (OR = 1,06). Em ambas as áreas, a chance de referir hipertensão arterial sistêmica aumentou com a idade, foi maior entre as mulheres, ex-fumantes, migrantes, portadores de morbidade, os de cor/raça não branca e portadores de plano de saúde. Também nas duas áreas, a hipertensão arterial sistêmica foi menor entre os trabalhadores e diminuiu com o aumento do número de anos de estudo. Todas as variáveis se mostraram associadas com hipertensão arterial sistêmica autorreferida, em ambas as áreas, entretanto puderam ser observadas diferenças nas magnitudes em sexo e faixa etária. Essas diferenças podem auxiliar na melhor forma de intervir nos serviços de prevenção e acesso de cada população.